Family and Healthcare Worker Participation in Promoting Exclusive Breastfeeding among Mothers - Farida Linda Sari Siregar; Nur Afi Darti; Nurbaiti Nurbaiti (Poltekkes Kemenkes Tanjung Karang, 2024)
The family greatly influences the mother's desire to practice exclusive breastfeeding to the baby and strongly influences the decision to breastfeed. Support from health worker professionals like nurses, doctors, cadre health professionals, and midwives can also help in the exclusive application of breast milk. This study uses an approach study quantitative. This study aims to identify family and health workers' participation in practice exclusive breastfeeding to mothers breastfeeding at the Medan Sunggal Community Health Center. This study's population is mothers with babies aged 0-24 months: retrieval technique purposive sampling sample, as many as 90 people. Research results show that the majority aged 20-35 years, as many as 71 people (78.9%), have the child more than 1 (multiparous), as many as 69 (76.7%), educated middle school (high school equivalent ), as many as 61 (68.7%), no work as many as 82 people (91.1%) and gave exclusive breast milk as many as 77 (85.6%). Research results show that families participate in practice exclusive breastfeeding to the mother by providing informational support in a way good (56.7 %), instrumental support good (84.4%), support emotional in a way good (61.1%), and support award in a way good (75.6%). The research results also show that significant health workers follow participation with good-to-mother breastfeeding during pregnancy (87.8%), when giving birth (80%), and during the postpartum period (77.8%). So it is concluded that the big family and health workers participate in practice exclusive breastfeeding to the mother.